2022
DOI: 10.47992/ijcsbe.2581.6942.0207
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Construction Projects: A Comparison between Users Committees and Contractor Approach

Abstract: Purpose: The policymakers are found to be undecided which assures the need for a refined policy on local governance in the formation of a user committee. It is expected to be beneficial for the project management team to point out the factors that directly or indirectly affect project performance. To assess the effectiveness of the construction projects implemented through Users Committees in comparison to the Contract Approach. Design/Methodology/Approach: The number of Informal Consultations was conducted at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…So, the results indicated that contract approach was found more preferable. Similar results were found on the basis on SWOT Analysis also [27].…”
Section: Analysis Of Construction Approach Usedsupporting
confidence: 87%
“…So, the results indicated that contract approach was found more preferable. Similar results were found on the basis on SWOT Analysis also [27].…”
Section: Analysis Of Construction Approach Usedsupporting
confidence: 87%